Knowledge-Oriented Leadership, Critical Psychological States, and Positive Work Attitudes: Moderating Role of Managerial Coaching - Shahida Mariam; Kausar Fiaz Khawaja; Muhammad Nawaz Qaisar; Mahmoona Khalil (NUST Journal of Social Sciences and Humanities)
Using the psychological capital theory from micro-coaching perspectives, this research examined the interactive effects of knowledge-oriented leadership and managerial coaching on employees' critical psychological states leading to positive work attitudes. A survey of 156 librarians, information managers, and library assistants from various public and private tertiary colleges in Punjab, Pakistan, was conducted using existing measures. Results revealed that knowledge-oriented leadership enhances critical psychological states (meaningfulness, safety, and availability), fostering positive work attitudes (creative self-efficacy, affective commitment, and work engagement). Managerial coaching moderated these relationships, amplifying the effect of knowledge-oriented leadership on critical psychological states and cultivating more positive work attitudes, particularly for employees who received higher levels of coaching. The findings underscore the importance of employee-centered leadership and development approaches in enhancing the psychological capital of employees and their outcomes at work. The implications of these findings are discussed.